Outcomes Associated with Time in Therapeutic Range for Patients Receiving Intravenous Unfractionated Heparin - Mujtaba Mahmud PharmD; Maia Klimatcheva PharmD; Angela Tsang PharmD; Andrew La PharmD; Victoria Miklus PharmD; Jack Becker PharmD; Benjamin Herrmann PharmD; Amanda Cremeans PharmD; Neal J Benedict PharmD; Carlo J Iasella PharmD, MPH, BCPS; Roy E Smith MD; James C Coons PharmD, FCCP, FACC, BCCP (Clinical and Applied Thrombosis/Hemostasis)
Time in therapeutic range (TTR) with intravenous unfractionated heparin (UFH) and its association with outcomes is poorly explored. UFH can be monitored with anti-Xa or aPTT, however, evidence indicates anti-Xa monitoring of UFH improves time to therapeutic anticoagulation. The objective of this study was to determine if TTR correlates with thrombotic and safety outcomes for patients receiving UFH, and if differences exist between these methods of monitoring. This retrospective, single center, cohort study stratified patient admissions based on the laboratory monitoring technique used (aPTT vs anti-Xa). The primary outcome was the presence of a new thrombotic event (TE) during the index visit. The secondary outcome was major bleeding during the index visit. Clinical outcomes were each assessed for their association with TTR. TTR was defined as the percentage of time in therapeutic range for each patient, as determined via the linear interpolation method. Of 4773 patient admissions (aPTT, n = 2,939, anti-Xa, n = 1834), TE occurred in 6.5% and 4.6% of visits in the aPTT and the anti-Xa cohort, respectively (p = .006). Bleeding events occurred in 33.3% and 31.6% of visits in the aPTT and the anti-Xa cohort, respectively (p = .204). TTR was 41.6% [IQR 23.3-57.7%] in the aPTT cohort compared to 56.1% [IQR 33.5-75.2%] in the anti-Xa cohort (p < .001). The monitoring of IV UFH with anti-Xa was associated with significantly fewer TEs and greater overall TTR when compared to those monitored with aPTT.